KMT2A regulates the autophagy-GATA4 axis through METTL3-mediated m6A modification of ATG4a to promote NPCs senescence and IVDD progression - Ouqiang Wu; Yuxin Jin; Zhiguang Zhang; Hao Zhou; Wenbin Xu; Linjie Chen; Morgan Jones; Kenny Yat Hong Kwan; Jianyuan Gao; Kai Zhang; Xiaofei Cheng; Qizhu Chen; et al. (Bone Research)
Abstract Intervertebral disc degeneration (IVDD), a disease associated with ageing, is characterised by a notable increase in senescent nucleus pulposus cells (NPCs) as IVDD progresses. However, the specific mechanisms that regulate the senescence of NPCs remain unknown. In this study, we observed impaired autophagy in IVDD-NPCs, which contributed to the upregulation of NPCs senescence and the senescence-associated secretory phenotype (SASP). The dysregulated SASP disrupted NPCs viability and initiated extracellular matrix degradation. Conversely, the restoration of autophagy reversed the senescence phenotype by inhibiting GATA binding protein 4 (GATA4). Moreover, we made the novel observation that a cross-talk between histone H3 lysine 4 trimethylation (H3K4me3) modification and N6-methyladenosine(m6A)-methylated modification regulates autophagy in IVDD-NPCs. Mechanistically, lysine methyltransferase 2A (KMT2A) promoted the expression of methyltransferase-like 3 (METTL3) through H3K4me3 modification, whereas METTL3-mediated m6A modification reduced the expression of autophagy-associated 4a (ATG4a) by attenuating its RNA stability, leading to autophagy damage in NPCs. Silencing KMT2A and METTL3 enhanced autophagic flux and suppressed SASP expression in IVDD-NPCs. Therefore, targeting the H3K4me3-regulated METTL3/ATG4a/GATA4 axis may represent a promising new therapeutic strategy for IVDD.